1995
DOI: 10.3382/ps.0740648
|View full text |Cite
|
Sign up to set email alerts
|

Polyacrylamide Gel Electrophoretic Patterns of Chicken Serum in Acute Inflammation Induced by Intramuscular Injection of Turpentine

Abstract: To develop a method to detect hidden inflammation using serum protein in chickens, changes in serum proteins with acute inflammation were analyzed using a turpentine-induced inflammation model. Inflammation in the pectoral muscle of a 14-wk-old White Leghorn became apparent 3 h after the injection of turpentine and became more severe thereafter. Coincident with the development of inflammation, changes in serum proteins were analyzed by electrophoresis on polyacrylamide gradient gels. The electrophoretic patter… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
17
0

Year Published

2001
2001
2017
2017

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(20 citation statements)
references
References 29 publications
3
17
0
Order By: Relevance
“…Distinct positive APPs from some species do not react in the same way in other species; serum amyloid P-component (SAP) is an APP in the mouse, but not in man, and CRP reacts as APP in several monogastric species, but not very well in small ruminants . Transferrin, which is a negative APP of most mammalian species, reacts as positive APP in chicken (Hallquist and Klasing, 1994;Tohjo et al, 1995).…”
Section: Positive Acute Phase Proteinsmentioning
confidence: 99%
See 1 more Smart Citation
“…Distinct positive APPs from some species do not react in the same way in other species; serum amyloid P-component (SAP) is an APP in the mouse, but not in man, and CRP reacts as APP in several monogastric species, but not very well in small ruminants . Transferrin, which is a negative APP of most mammalian species, reacts as positive APP in chicken (Hallquist and Klasing, 1994;Tohjo et al, 1995).…”
Section: Positive Acute Phase Proteinsmentioning
confidence: 99%
“…It was discovered due to its binding to the C-polysaccharide of 1999) and birds after lipopolysaccharide (LPS), turpentine and croton oil studies in domestic fowl (Patterson and Mora, 1964;1965;Hallquist and Klasing, 1994;Tohjo et al, 1995;Takahashi et al, 1997;Nakamura et al, 1998;Chamanza et al, 1999a;Adler et al, 2001;Xie et al, 2002;Upragarin, 2005) and LPS and haemorrhagic enteritis virus investigations in turkey (Mazur-Gonkowska et al, 2004). For avian cytokines the reader is referred to (Lynagh et al, 2000;Sijben et al, 2003;Leshchinsky and Klasing, 2003;Abdalla et al, 2004;Kaiser et al, 2004;2005) pneumococci.…”
Section: Function Of Positive Acute Phase Proteinsmentioning
confidence: 99%
“…In poultry, the measurement of APP serum levels may be useful when monitoring health conditions (Tohjo et al, 1995) and characterizing muscle lesions present in areas where inspection is comparatively complex after slaughter (Saini e Webert, 1991). However, it should be noted that establishing severity and chronic nature of any lesion diagnosed in poultry meat prior to slaughter is essential as a measure to prevent health problems to consumers (Chamanza et al, 1999).…”
Section: A Eletroforese De Proteínas é Um Método Relativamente Simplementioning
confidence: 99%
“…Altered health status of birds often results in measurable changes in blood biochemistry (Hurwitz and Griminger 1961;Okumura and Tasaki 1969), measuring plasma levels of certain acute-phase proteins (Kushner and Mackiewiez 1987;Singh 1988;Saini and Webert 1991;Takahashi et al 1994;Tohyo et al 1995Tohyo et al , 1996, including the SAA protein also (Chamanza et al 1999;Gruys et al 2005), could be useful in monitoring poultry health. It has been suggested that increased circulating proteolytic cleavage of SAA may potentially contribute to the development of AA amyloid deposition (Migita et al 1996).…”
Section: Introductionmentioning
confidence: 99%